Registration of 'CP 10‐2195' Sugarcane. Issue 3 (1st September 2019) - Islam, Md S.; McCord, Per; Sandhu, Hardev S.; Zhao, Duli; Davidson, R. Wayne; Gordon, Vanessa; Sood, Sushma; Comstock, Jack C.; Singh, Maninder P.; Baltazar, Miguel
Abstract : 'CP 10‐2195' (Reg. no. CV‐192, PI 690763) sugarcane (a complex hybrid of Saccharum spp.) was advanced through cooperative research conducted by the USDA‐ARS, the University of Florida, and the Florida Sugarcane League, Inc., and released to growers in June 2018 for use on sand soils in Florida. It was selected from a polycross made at Canal Point (CP) with the sugarcane breeding line CP 01‐2390 as the female parent. CP 10‐2195 was released by the Florida Sugarcane Variety Committee because of its high cane and sucrose yields, high commercial recoverable sucrose on sand soils, and resistance to brown rust, leaf scald, Sugarcane mosaic virus strain E, Sugarcane yellow leaf virus, ratoon stunt, and smut and its moderate resistance to orange rust. Based on results from 12 harvests at four locations in final‐stage replicated yield trials, CP 10‐2195 had 23.0 and 29.1 % higher cane and sucrose yields, respectively, than the check 'CL 88‐4730'. While it did not differ significantly from 'CP 96‐1252' in either cane or sucrose yield, CP 10‐2195 displayed superior resistance to brown rust. CP 10‐2195 is considered to have moderate tolerance to freeze on the basis of field tests for progressive sugar degradation.